2015
DOI: 10.1002/ange.201509973
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Multiply Substituted Polycyclic Aromatic Hydrocarbons by Iridium‐Catalyzed Annulation of Ring‐Fused Benzocyclobutenol with Alkyne through C−C Bond Cleavage

Abstract: The first iridium-catalyzed intermolecular cyclization between alkynes and ring-fused benzocyclobutenols (RBCB) through CÀCb ond cleavage is described. Av ariety of elusive polycyclic aromatic hydrocarbons (PAHs) with multiple substituents are obtained in good yields under mild conditions.This procedure provides aunique and expeditious tool for the synthesis of PAHs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 53 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Further, the proposed catalytic cycle has been depicted in scheme 41, where the reaction was initiated with the generation of active Ir-catalyst A, from the Ir-dimer complex. Then 53 Where the metal coordinates through free -OH for the insertion between C-C bond to generate the M-C bond. The authors examined the scope of the reaction, which revealed the general trend in the reactivities of the substrates and alkynes.…”
Section: Various Transition Metal-catalyzed Unusual Reactions Of Alkynementioning
confidence: 99%
“…Further, the proposed catalytic cycle has been depicted in scheme 41, where the reaction was initiated with the generation of active Ir-catalyst A, from the Ir-dimer complex. Then 53 Where the metal coordinates through free -OH for the insertion between C-C bond to generate the M-C bond. The authors examined the scope of the reaction, which revealed the general trend in the reactivities of the substrates and alkynes.…”
Section: Various Transition Metal-catalyzed Unusual Reactions Of Alkynementioning
confidence: 99%
“…In comparison, owing to a surrounding environment composed of four bonding atoms, regioselective alkyl deconstructive carbofunctionalization has at present remained a challenging but highly valuable topic in synthetic chemistry, as this process would offer the potential to develop novel transformations producing functional molecules that are difficult to prepare or inaccessible by conventional approaches (Liu et al., 2018). For instance in this regard, the Zhu group has reported a number of transformations on the cleavage of strained alkyl chains such as cyclobutanols (Ren et al., 2015, Ren et al., 2016, Yu et al., 2016, Zhao et al., 2015). Very recently, Roque et al.…”
Section: Introductionmentioning
confidence: 99%